Excited-State Proton Transfer in 8-Azapurines I: A Kinetic Analysis of 8-Azaxanthine Fluorescence - Jacek Wierzchowski; Bogdan Smyk (Molecules, 2020)
A super-continuum white laser with a half-pulse width of ~75 ps was used to observe the kinetics of a postulated excited-state proton transfer in 8-azaxanthine and its 8-methyl derivative. Both compounds exhibited dual emissions in weakly acidified alcoholic media, but only one band was present in aqueous solutions, exhibiting an abnormal Stokes shift (>12,000 cm−1). It was shown that long-wavelength emissions were delayed relative to the excitation pulse within alcoholic media. The rise time was calculated to be 0.4–0.5 ns in both methanol and deuterated methanol. This is equal to the main component of the fluorescence decay in the short-wavelength band (340 nm). Time-resolved emission spectra (TRES) indicated a two-state photo-transformation model in both compounds. Global analysis of the time dependence revealed three exponential components in each compound, one of which had an identical rise-time, with the second attributed to a long-wavelength band decay (6.4 ns for aza-xanthine and 8.3 ns for its 8-methyl derivative). The origin of the third, intermediate decay time (1.41 ns for aza-xanthine and 0.87 ns for 8-methyl-azaxanthine) is uncertain, but decay-associated spectra (DAS) containing both bands suggest the participation of a contact ion pair. These results confirm the model of phototautomerism proposed earlier, but the question of the anomalous isotope effect remains unsolved.